2016
DOI: 10.1080/17470919.2016.1160953
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about human agency influence the neural processing of gaze during joint attention

Abstract: The current study measured adults' P350 and N170 ERPs while they interacted with a character in a virtual reality paradigm. Some participants believed the character was controlled by a human ("avatar" condition, n = 19); others believed it was controlled by a computer program ("agent" condition, n = 19). In each trial, participants initiated joint attention in order to direct the character's gaze toward a target. In 50% of trials, the character gazed toward the target (congruent responses), and in 50% of trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…These findings are corroborated by a number of other previous and subsequent findings . For instance, a recent study using an established gaze cueing paradigm reported increased activation in bilateral TPJ for gaze following when participants thought the gaze had human origins compared to a preprogrammed, computer‐determined origin …”
Section: Impact Of Knowledge Cues the Human Observersupporting
confidence: 85%
“…These findings are corroborated by a number of other previous and subsequent findings . For instance, a recent study using an established gaze cueing paradigm reported increased activation in bilateral TPJ for gaze following when participants thought the gaze had human origins compared to a preprogrammed, computer‐determined origin …”
Section: Impact Of Knowledge Cues the Human Observersupporting
confidence: 85%
“…This is also found when avatar-gaze is believed to be controlled by a human rather than when it is believed to be fully robot-controlled (Wykowska, Wiese, Prosser, & Müller, 2014). Likewise, joint attention is initiated and responded to differently when an avatar face in a virtual reality environment is believed to be human-controlled (Caruana, Lissa, & McArthur, 2017a;Caruana, Spirou, & Brock, 2017c;Wykowska, Wiese, Prosser, & Müller, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…This seems to affect brain responses as well, where human-controlled avatars (i.e. supposedly another human participant controls the avatar's eyes) elicit differential ERP responses, but also lead to different behavioral responses to gaze cues (Caruana, Lissa, et al, 2017a;Caruana, Spirou, et al, 2017c;Wykowska et al, 2014). A study by Singer et al (2004) showed that perceived intentionality activated the bilateral insula.…”
Section: Ascribed Intentionality Of Social Feedbackmentioning
confidence: 99%
“…demonstrated reduced gaze following when gaze cues were perceived as being delivered by a robot (e.g., a computer program performing predetermined behaviors) rather than a human agent . These effects are reflected in neural activity, with increased activation of the TPJ when gaze is perceived as human controlled, and reduced magnitudes of the event‐related P1 and N170 components when gaze is perceived as computer controlled.…”
Section: The Three Core Processesmentioning
confidence: 99%